Evaluation of composting performance of mixtures of chicken blood and maize stover in Harare, Zimbabwe - Charity Pisa; Menas Wuta (International Journal of Recycling of Organic Waste in Agriculture)
Background: Chicken processing results in the production of a lot of blood which if disposed on land poses environmental hazards in terms of land pollution. The aim of the study was to develop an aerobic composting process for chicken blood to produce a nitrogen-rich soil amendment for use in agriculture. The study involved composting of blood and maize stover of different proportions (10%, 30%, 70% and 100% maize stover) in compost bins over 72 days and determining which proportions would yield compost with greater potential to support plant growth. Results: The performance of the different compost mixtures was evaluated by monitoring internal temperature, mineral N (NH4 + -N and NO3 â -N), C/N ratio, pH, electrical conductivity and total cations. The concentration of ammonium N decreased by 8.75%, 50.5%, 33.5% and 18.8% for the 10%, 30%, 70% and 100% stover treatments, respectively, with composting time. Nitrate N peaked to 1.93 and 1.06 mg/kg for the 30% and 70% treatments, respectively, on day 43, while it peaked to 1.54 and 0.54 mg/kg for the 10% and 100% treatments, respectively, on day 50. The C/N ratios decreased significantly (p < 0.001) for all treatments. Conclusion: The 10% and 30% treatments had better composting performance than the 70% and 100% treatments as they reached and maintained thermophilic temperatures for at least 8 days. The 10% and 30% treatments appeared to have the greater potential of supporting crop growth.